2021
DOI: 10.1108/pijpsm-01-2021-0001
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for post-traumatic stress among New Zealand police personnel: a cross sectional study

Abstract: PurposeThe purpose of this research was to examine which factors increase the risk of post-traumatic stress in police officers to assist with identifying strategies that will minimize its occurrence.Design/methodology/approachThis study of constabulary and non-constabulary members of the New Zealand Police has been based on an 80-question electronic survey, which was sent to all serving, resigned and retired members of the New Zealand Police Association, which number approximately 18,000. The survey included a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Further analyses of the research data found that the longer officers are unfit for work, the more they are affected by these types of problems (Ellrich and Baier, 2016). The long-term effect of the problems experienced can lead to PTSD, which can include nightmares, withdrawal, avoidance behavior, and psychosomatic complaints, such as anxiety and disturbed sleep patterns (den Heyer, 2021; Gasch, 2000; Sab et al, 2003; Schneider and Latscha, 2010).…”
Section: The Effect Of An Assault On a Police Officermentioning
confidence: 99%
See 1 more Smart Citation
“…Further analyses of the research data found that the longer officers are unfit for work, the more they are affected by these types of problems (Ellrich and Baier, 2016). The long-term effect of the problems experienced can lead to PTSD, which can include nightmares, withdrawal, avoidance behavior, and psychosomatic complaints, such as anxiety and disturbed sleep patterns (den Heyer, 2021; Gasch, 2000; Sab et al, 2003; Schneider and Latscha, 2010).…”
Section: The Effect Of An Assault On a Police Officermentioning
confidence: 99%
“…An assault on a police officer can have a negative effect on the officer, not only physically, but also psychologically, and the impact can extend to others besides the assaulted officer (Redman, 2018). Physical injuries arising from being assaulted can range from minor to life-threatening, while psychological injuries can range from emotional strain to post-traumatic stress disorder (PTSD) (den Heyer, 2021; Carlier et al, 1997; Maguen et al, 2009; McCaslin et al, 2006). Such psychological injuries can be devastating, can have a long-term effect on police officers' performance in future confrontations (Boylen and Little, 1990), and an impact on their relationships with their colleagues and family members, often causing stress and anxiety for their partners and children (Redman, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As first responders, police officers face a work environment laden with traumatic events, violence, armed conflicts, and exposure to serious injuries [ 2 , 3 ]. Within their initial 6 months, officers often encounter an average of three traumatic incidents, with constant exposure to violence, night shifts, and a demanding environment, increasing the risk of stress and psychological issues [ 4 , 5 ]. This high-risk occupational group is susceptible to mental health challenges and physical ailments when compared to the general population [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…den Heyer, 2021;Ko & Memon, 2022;Kyron et al, 2022;Regehr et al, 2021). Police play a central role in all stages of the CJS, from law enforcement and investigation through to prosecution.…”
Section: Statement Of Purposementioning
confidence: 99%
“…Much of the existing literature on police and legal professional wellbeing consists of quantitative surveys on wellbeing and self-reported symptoms (e.g. den Heyer, 2021;Leclerc et al, 2020;Varker et al, 2023;Vrklevski & Franklin, 2008). The limited body of qualitative research has focused on the specific impacts of PTM exposure on wellbeing (Burns et al, 2008;R.…”
Section: Statement Of Purposementioning
confidence: 99%